Importance of the female reproductive tract microbiome and its relationship with the uterine environment for health and productivity in cattle: A review - Ault-Seay, Taylor B.; Moorey, Sarah E.; Mathew, Daniel J.; Schrick, F. Neal; Pohler, Ky G.; McLean, Kyle J.; Myer, Phillip R. (Frontiers in Animal Science, 2023)
Once thought to be sterile, the reproductive tract microbiome has been characterized due to the transition from culture-dependent identification of bacteria to culture-independent sequencing methods. The urogenital microbiome was first identified in women through the Human Microbiome Project, which led to research in other species such as the bovine. Previous research focused on uterine bacteria associated with postpartum disease, but next generation sequencing methods identified a normal, healthy bacterial community of the reproductive tract of cows and heifers. Bacterial communities are now understood to differ between the uterus and vagina, and throughout the estrous cycle with changes in hormone dominance. In a healthy state, the bacterial communities largely interact with the uterine environment by assisting in maintaining the proper pH, providing and utilizing nutrients and metabolites, and influencing the immunological responses of the reproductive tract. If the bacterial communities become unbalanced due to an increase in potentially pathogenic bacteria, the health and fertility of the host may be affected. Although the presence of a reproductive tract microbiome has become widely accepted, the existence of a placental microbiome and in utero colonization of the fetus is still a popular debate due to conflicting study results. Currently, researchers are evaluating methods to manipulate the reproductive bacterial communities, such as diet changes and utilizing probiotics, to improve reproductive outcomes. The following review discusses the current understanding of the reproductive tract microbiome, how it differs between humans and cattle, and its relationship with the uterine environment.